Evaluasi Pengaruh Keamanan Data Dan Kepercayaan Pelanggan Pada Website E-Commerce PT. XYZ - Firman Eko Purnomo; Ari Kusyanti; Himawat Aryadita (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
XYZ is a Joint-venture between PT. Telkom Indonesia and eBay. Have a concept as Online-Marketplace. Number of users of e-commerce website PT. XYZ in 2017 in Indonesia for more than 1,000,000 users. This study aims to determine what factors affect the acceptance of e-commerce website PT. XYZ, the variables used are the variables of the Unified Theory of Acceptance and Use of Technology (UTAUT) model and other variables that include trust and perceived security. This research uses parametric method. For data collection methods using an online questionnaire. As for the sampling technique using probability sampling technique is simple random sampling with the minimum number of samples using the formula Hair et. Al. Data obtained from 138 respondents and data to be used in this study for 111. Furthermore, the data have been collected to test the basic assumptions and test the classical assumptions of normality, homogeneity, multicollinearity, heteroscedasticity and autocorrelation. Data that passed the assumption of basic and classical tests carried out parametric analysis using multiple linear regression. The results showed that not all variables studied significantly influence the behavioral intention e-commerce website PT. XYZ. The variables that have significant influence are Social Influence and Perceived Security.